GIGI: The Research Bulletin for School of Dental Sciences - Ahmad, Azlina (School of Dental Sciences, 2016)
Welcome to the first issue of, GIGI, The Research Bulletin for School of Dental Sciences, USM our primary aim is to feature research activities and achievements related to our projects to signify our presence in the academic domain. It is high time for us to keep our peers informed and updated on some events that have happened in the School of Dental Sciences pertaining to research and innovation. We intend to publish this bulletin twice a year to cater for the rather large number of ongoing research activities in our school. It is meant to highlight the profile of our staff, their achievements in research, latest information on grant availability, research progress, products, awards and publications in national and international journals. besides. It will also focus on sharing the experience of our academic staf in their involvement in research collaboration, academic partnership. community work and social responsibility.